Computational Software: Simple FMM Libraries for Electrostatics, Slow Viscous Flow, and Frequency-Domain Wave Propagation (Communications in Computational Physics, 2018)
We have developed easy to use fast multipole method (FMM) libraries forthe Laplace, low-frequency Helmholtz, and Stokes equations in two and three dimensions.The codes are based on a new method for applying translation operators andprovide reasonable performance on either single core processors, or small multi-coresystems using OpenMP.